Factors Influencing Kidney Transplantation Experiences for Patients From Culturally and Linguistically Diverse Backgrounds: A Qualitative Study - Kimberley Crawford; Catherine Wilson; William R. Mulley; Nigel D. Toussaint; Elaine Kennedy; Narissa Andrew; Andrea Ward; Mandy Truong (Wiley, 2024)
ABSTRACT Background Disparities in aspects of chronic kidney disease progression and management exist for patients from culturally and linguistically diverse (CALD) backgrounds, including with treatment and outcomes for kidney transplantation. Objective This study aimed to explore factors that impact kidney transplant outcomes from the perspective of kidney transplant recipients (KTRs) from CALD backgrounds and their family caregivers. Methods A descriptive qualitative design was utilised. Participants were recruited from two tertiary hospitals in Victoria, Australia. Semi‐structured interviews were conducted with KTRs who were born overseas in countries where English is not the primary language. Interviews were also conducted with family caregivers. Analysis was guided by the Framework Method, and emergent subcategories were mapped into the categories identified in Andersen's Health Service Utilisation Model. Results Data from 21 KTRs and five caregivers were grouped under the categories of Population Characteristics, Environment, Health Behaviour and Outcomes. KTRs believed that neither culture nor religious beliefs impacted how they managed their transplant or healthcare utilisation. KTRs expressed satisfaction with their care, felt no inequity with how they were treated by health professionals and expressed gratitude for the Australian healthcare system. Language did not necessarily impact transplant outcomes, but there was a reliance on interpreters for non‐English‐speaking patients as most written information was in English. Caregivers were instrumental in providing support but discussed the challenges involved. Conclusion This study explored factors influencing kidney transplantation for KTRs from a CALD background. The study provided insight into how to deliver quality healthcare to these patients, highlighting the importance of health services providing information that is written in the patient's own language and respectively asking KTRs about their health beliefs or customs. Caregivers were instrumental in supporting KTRs, but there is a need to better prepare them for this role. Patient or Public Contribution Patient and public involvement was integrated into the design and delivery of the study. KTRs from CALD backgrounds assisted with framing the research questions and offering advice on the recruitment and data collection process.